Appraisal analysis and AI chatbots - Križan, Agata (ELOPE (Ljubljana), 2025)
Artificial intelligence (AI) is rapidly transforming various fields, including linguistics, by offering new tools for the analysis and generation of human language. As AI tools, particularly chatbots, have become increasingly sophisticated, questions have arisen about their capacity to replicate complex human linguistic processes, such as those covered by the appraisal framework developed by Martin and White (2005). The appraisal framework examines how three main categories – attitude, graduation, and engagement – are expressed in discourse at the semantic level. This paper investigates how AI chatbots, MS Copilot, ChatGPT, and Claude approach appraisal analysis in a selected text, highlighting similarities and notable differences in comparison to human analysis. The findings, although based on analysis of a single text, provide valuable insights into the advantages and drawbacks of AI in mimicking human-like appraisal analysis, which might be beneficial when conducting appraisal research.
Keywords: appraisals; ChatGPT; Claude; human and AI comparative analyses; jezik vrednotenja; MS Copilot; primerjalne analize; umetna inteligenca